Hubungan Keyakinan Manfaat dan Kemudahan Dengan Kelengkapan Pengisian Rekam Medis - Devhy, Ni Luh Putu; Purwanti, Ika Setya; Faidah , Nurul (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
Confidence in convenience and confidence in the benefits of filling out medical records are important, if we feel confident about the benefits, automatically filling out medical records completely. Incomplete filling of medical records can cause harm to health services, if something unexpected happens. The medical record is said to be complete if all the indicators contained in the cheek list are filled out completely, the medical record is said to be incomplete if one indicator is not filled in, so there are still many hospitals that get incomplete scores below 100%. Based on this description, the purpose of this study is to determine the relationship between usefulness beliefs and convenience beliefs with the completeness of filling out medical records. This research is an observational study with a cross sectional study design. This research was conducted at Dharma Yadnya General Hospital, within a period of 3 months, namely, January 2022-March 2022, the population of this study were doctors and medical records. The sample selection used non-probability sampling method, for the selection of samples in the medical record using the accidential sampling method. Collecting data using a questionnaire and a cheek list completeness of filling out medical records. The results obtained in this study are that there is no relationship between the belief in the benefits and the belief in convenience with the completeness of filling out the medical record with a p value of 0.164 and a p value of 0.109. Based on the results of this study, even though the belief in the benefits and convenience is good, it does not mean that the health worker fills out the medical record completely, this of course requires consistency and time in filling out the medical record, if the hospital can provide SPO related to filling out the medical record.